Rapid, high-precision measurements of boron isotopic compositions in marine carbonates - McCulloch, M.; Holcomb, M.; Rankenburg, Kai; Trotter, J. (John Wiley & Sons Ltd, 2014)
Copyright © 2014 John Wiley & Sons, Ltd. RATIONALE The isotopic composition and elemental abundance of boron (B) in marine carbonates provide a powerful tool for tracking changes in seawater pH and carbonate chemistry. Progress in this field has, however, been hampered by the volatile nature of B, its persistent memory, and other uncertainties associated with conventional chemical extraction and mass spectrometric measurements. Here we show that for marine carbonates, these limitations can be overcome by using a simplified, low-blank, chemical extraction technique combined with robust multi-collector inductively couple plasma mass spectrometry (MC-ICPMS) methods. METHODS Samples are dissolved in dilute HNO3 and loaded first onto on a cation-exchange column with the major cations (Ca, Mg, Sr, Na) being quantitatively retained while the B fraction is carried in the eluent. The eluent is then passed directly through an anion column ensuring that any residual anions, such as SO42-, are removed. Isotopic measurements of 11B/10B ratios are undertaken by matching both the B concentration and the isotopic compositions of the samples with the bracketing standard, thereby minimising corrections for cross-contamination. RESULTS The veracity of the MC-ICPMS procedure is demonstrated using a gravimetrically prepared laboratory standard, UWA24.7, relative to the international reference standard NIST SRM 951 (d11B = 0‰). This gives values consistent with gravimetry (d11B = 24.7 ± 0.3‰ 2sd) for solutions ranging in concentration from 50 to 500 ppb, equivalent to ~2-10 mg size coral samples. The overall integrity of the method for carbonate analysis is demonstrated by measurements of the international carbonate standard JCp-1 (d11B = 24.3 ± 0.34‰ 2sd). CONCLUSIONS A streamlined, integrated approach is described here that enables rapid, accurate, high-precision measurements of boron isotopic compositions and elemental abundances in commonly analysed biogenic carbonates, such as corals, bivalves, and large benthic forams. The overall simplicity of this robust approach should greatly facilitate the wider application of boron isotope geochemistry, especially to marine carbonates.